Research on structural dynamic characteristics of continuous steel box girder-bridge with lager ratio of wide-span - Yin Haijun; Li Ziqing; Hao Xianwu (ITM Web of Conferences, 2018)
Structure natural frequency and mode of vibration can not only reflect the structure modal parameters of dynamic properties, but also incarnate the dynamic evaluation characteristics of bridge structure. This paper applies ANSYS to establish the finite element model based on a continuous steel box girder bridge in order to obtain the corresponding modal analysis parameters. Through the environmental stimulation test, The results show that height of the steel box girder and the setting of diaphragm plate is reasonable, transverse space of piers not merely provide enough support but also ensure lateral stability of the bridge, as well as offering aside the maximum lateral clearance of the existing road. Meanwhile, the calculation results have important engineering practical values. which can provide basic data for the design, construction and maintenance of similar Bridges.